Municipal solid waste: zero tolerance management strategy. (1st January 2014) - Goyal, Devendra; Kumar, Sunil; Sil, Avick
Currently, Indian cities generate waste which is being disposed in its outskirt as open dumping. This approach affects health and life of people living at city outskirts. A paradigm shift is required in the approach to waste management. Waste management policy should aim at scientific processing of waste within the city itself. This paper highlights policy framework towards management of biodegradable waste through biogas plants and its advantages. Based on the current challenges faced by municipal authorities, solution based matrix planning has been reported. Incentive and subsidy scheme along with support from different section of society and government bodies has been widely discussed and dissipated in this paper.